Enriching the content of foreign medical students’ independent work by on-line courses on the edx platform. - Gura, O. I.; Ragrina, Z. M.; Гура, О. І.; Рагріна, Жанна Михайлівна (My University, 2021)
The article explores the benefits of using computer technology in the educational process and emphasizes their ability to increase the motivation of foreign medical students to study. Using the latest technologies in the educational process is a demand of time. Intensifying the interest to the discipline and improving the quality and level of knowledge of students is the purpose of such using. The necessity and importance of on-line education at the current stage of society development is substantiated. Using effective techniques and methods of online learning, creating a variety of online courses, engaging students in an independent creative process – this is the optimal way to update the internal reserves of the educational process. The role of students' independent work in the educational process is determined. It is moticed that the independent work of students requires the same organization and methodological support as the traditional class work. The peculiarities of the content of independent work of foreign medical students are revealed and their communicative needs are determined. In accordance with the subjects of the educational programs for specialists in the field of knowledge 22 "Health care", specialty 222 "Medicine" and according to the communication needs, EDX on-line platform was selected and created for creating and implementing online special courses for independent work of foreign students at different stages of study. The structure of individual online special courses is analyzed, the purpose, tasks and results of each of them are highlighted. The subject, distribution of classes, structure, linguistic, speech and communication material of the on-line special course "Introduction to the specialty: scientific speech" are characterized. The specificity, orientation, purpose and specifics of the task of the on-line special course "Professional communication: doctor – patient" are revealed. The conclusions about the necessity and appropriateness of the application of the specified online special courses in the process of preparation of foreign students in medical institutions of higher education. У статті з’ясовано переваги застосування комп’ютерних технологій у навчальному процесі та наголошено на їхній здатності збільшувати мотивацію іноземних студентів медичних закладів вищої освіти до навчання. Використання новітніх технологій у навчальному процесі – вимога часу. Метою такого використання є посилення інтересу до дисципліни та підвищення якості та рівня знань студентів. Обґрунтовано необхідність та значущість онлайн-освіти на сучасному етапі розвитку суспільства. Використання ефективних прийомів та методів онлайн-навчання, створення різноманітних онлайн-курсів, залучення студентів до самостійного творчого процесу – це оптимальний шлях оновлення внутрішніх резервів навчального процесу. Визначено роль самостійної роботи студентів у навчальному процесі. Зазначено, що самостійна робота студентів вимагає такої ж організації та методичного забезпечення, як і традиційна аудиторна робота. Розкрито особливості змісту самостійної роботи іноземних студентів-медиків та визначено їхні комунікативні потреби. Згідно з тематикою навчальних програм підготовки спеціалістів фахівців галузі знань 22 «Охорона здоров’я», спеціальності 222 «Медицина» та відповідно до комунікативних потреб обрано та охарактеризовано дистанційну платформу еdX для створення та впровадження онлайн-спецкурсів для самостійної роботи іноземних студентів на різних етапах навчання. Проаналізовано структуру окремих онлайн-спецкурсів, виокремлено мету, завдання та результати кожного з них. Охарактеризовано тематику, розподіл занять, структуру, мовний, мовленнєвий та комунікативний матеріал дистанційного онлайн-спецкурсу «Вступ до спеціальності: наукове мовлення». Розкрито специфіку, спрямованість, призначення та особливості завдання дистанційного онлайн-спецкурсу «Професійне спілкування: лікар – хворий». Зроблено висновки про необхідність та доречність застосування зазначених онлайн-спецкурсів у процесі підготовки іноземних студентів у медичних закладах вищої освіти.
Збагачення змісту самостійної роботи іноземних студентів-медиків шляхом впровадження онлайн-спецкурсів на платформі edX.
Keywords: on-line technologies; on-line special course; edX platform; foreign medical students; онлайн-технології; онлайн-спецкурс; платформа edX; іноземні студенти-медики; онлайн-технологии; онлайн-спецкурс; платформа edX; иностранные студенты-медики